Obstetric morbidity among women in Eastern India: an analysis based on National Family and Health Survey 4 and 5 - Gupta, Nilanjana; Raj, Papia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Obstetric morbidities are one of the leading causes of maternal mortality and disease burden for women in the reproductive age group. The study aims to examine the geographical disparities and the impact of socioeconomic, reproductive determinants on obstetric morbidity. Methods: Two rounds of National Family and Health Survey (NFHS 4 and NFHS 5) data were used for analysis. The study was conducted in the eastern India covering four states that include Bihar, Jharkhand, Odisha, and West Bengal. Currently married women in 15-49 years age reporting at least one obstetric morbidity was considered. Bivariate and binary logistic regression analysis using both adjusted and unadjusted odds ratio were used to understand the influence and association of obstetric morbidity with socio-economic factors. Results: In eastern India, obstetric morbidity decreased from NFHS 4 to NFHS 5 by 6.79%. In both rounds, Odisha has a higher prevalence of any obstetric morbidity. This analysis shows lower age, higher education of women, belonging to rural areas, not having proper toilet facilities, higher birth order, and higher age at marriage and first birth increases the prevalence of obstetric morbidity among women in the eastern region during NFHS 4 and NFHS 5. Conclusions: Based on the analysis it can be contended obstetric morbidity in the eastern region was high. To address this issue, region/state specific programs, highlighting maternal/obstetric health awareness, along with regular monitoring and evaluation of ongoing maternal health programs are needed to target women suffering from obstetric morbidity.